2017
DOI: 10.1039/c6sm02414a
|View full text |Cite
|
Sign up to set email alerts
|

Transport and adsorption under liquid flow: the role of pore geometry

Abstract: We study here the interplay between transport and adsorption in porous systems with complex geometries under fluid flow. Using a lattice Boltzmann scheme extended to take into account the adsorption at solid/fluid interfaces, we investigate the influence of pore geometry and internal surface roughness on the efficiency of fluid flow and the adsorption of molecular species inside the pore space. We show how the occurrence of roughness on pore walls acts effectively as a modification of the solid/fluid boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…However, in the last decade, suitable model Boltzmann equations, living in discrete phase-space, have proven capable of incorporating the basic features which control the physics of multi-phase flows, namely a non-ideal equation of state, surface tension and disjoining pressure 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Some of the models or improved versions thereof, have been successfully used in the simulation of complex fluids such as polymers 24 , soft glassy materials 25 , liquid crystals 26,27 , and porous materials 28,29 . With the help of those LB multiphase models, a wide variety of multiphase problems, including wetting [30][31][32] , droplet dynamic and evaporation [33][34][35] , phase transition 9,17,36,37 , hydrodynamic instability 21 , etc., have been successfully simulated and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last decade, suitable model Boltzmann equations, living in discrete phase-space, have proven capable of incorporating the basic features which control the physics of multi-phase flows, namely a non-ideal equation of state, surface tension and disjoining pressure 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Some of the models or improved versions thereof, have been successfully used in the simulation of complex fluids such as polymers 24 , soft glassy materials 25 , liquid crystals 26,27 , and porous materials 28,29 . With the help of those LB multiphase models, a wide variety of multiphase problems, including wetting [30][31][32] , droplet dynamic and evaporation [33][34][35] , phase transition 9,17,36,37 , hydrodynamic instability 21 , etc., have been successfully simulated and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several descriptions and extensions of this method have since been proposed for various applications, see e.g. [33,35,36,[43][44][45][46]. In the present work, we show that this method can be used for charged mobile (hence experiencing diffusion, advection and migration) and adsorbing/desorbing species -a combination of features which had to date not been investigated previously despite its relevance in the many contexts described in the introduction.…”
Section: Moment Propagationmentioning
confidence: 60%
“…The pore structure and morphology at different scales affect the flow and transport properties. Variations in pore connectivity and tortuosity at the microscale may result in complex flow and transport behaviors [5,6]. Permeability and hydraulic conductivity are the characteristics most affected by the internal structure of the pores.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of the pore structure at the microscale increases the complexity and tortuosity resulting in complicated and anomalous transport behaviors [5,6]. A numerical simulation of diffusion in virtual porous media generated using the Boolean model showed that pore geometry affects the diffusion properties and non-Fickian behavior occurs at the continuum scale [16].…”
Section: Introductionmentioning
confidence: 99%